Family Business Gone Wrong? Ownership Patterns and Corporate Performance in Thailand - Akira Suehiro (Asian Development Bank Institute (ADBI), 2001)
Since the Asian currency and economic crises erupted in 1997, many scholars andinternational financial organizations have discussedtheir major causes and proposed policies thatcould overcome the structural weaknesses that apparently led to the crises.In this context, scholars atthe International Monetary Fund, World Bank and numerous otherinstitutions have emphasized theneed for Asian governments to bring about institutional reforms in corporate governance. However,they seem to have paid little attention to the important issue of how to effectively implement theseinstitutional reforms, keeping in mind thereality of Asian corporations rather than the Anglo-American ideal of good corporate governance.The World Bank, in general, and a group of researchers working at that institution, inparticular, have focused on identification of ultimate owners, agency problems, the large gap betweencontrol rights and cashflow rights, and expropriation of minority shareholders. However, it appearsthat in their analysis they have not taken into account the actual functioning of local Asian firms andtheir responses to government institutional reforms after the crisis.
hdl:11540/4124
Keywords: 330